Observations on trial by jury, with suggestions for the amendment of our present system - Houston, Arthur (Dublin Statistical Society, 1861)
In this paper, I propose briefly to examine:? 1. What is the fundamental principle of trial by jury, and what are the advantages resulting therefrom 2. The machinery by which the system is worked in this country and in England, and how its efficiency is thereby affected. 3. The defects, if any, existing in these institutions, and their remedies.
Read Monday, 15th April, 1861
Keywords: Trial by jury; 314.15